Viability of seed balls for large-scale restoration of native plant communities in New Zealand - James W. Griffiths; Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; Jennifer Alderton-Moss; Karin van der Walt; Anja McDonald; Kirsty Moran (New Zealand Journal of Botany, 2025)

Physical properties of seed ball formulations - Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; James W. Griffiths (New Zealand Journal of Botany, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The diversity, distribution, and temporal stability of coral ‘zooxanthellae’ on a pacific reef: from the scale of individual colonies to across the host community - Allison M. Lewis; Caleb C. Butler; Kira E. Turnham; Drew F. Wham; Kenneth D. Hoadley; Robin T. Smith; Dustin W. Kemp; Mark E. Warner; Todd C. LaJeunesse (Coral Reefs, 2024)

Validation of load based testing methodology for residential air conditioners and heat pumps - Parveen Dhillon; Drew Welch; Brian Butler; W. Travis Horton; James E. Braun (Energy and Buildings, 2023)

The Joy of birds: the effect of rating for joy or counting garden bird species on wellbeing, anxiety, and nature connection - Maria E. White; Iain Hamlin; Carly W. Butler; Miles Richardson (Urban Ecosystems, 2023)
The feeding of garden birds is a popular and accessible means of connecting with wildlife in urban environments in the United Kingdom. Past research has found that the main motivations for feeding birds are psychological benefits, concern for bird welfare, and connecting to nature. This study explores whether a brief birdwatching activity impacts on wellbeing, anxiety, and nature connection. One hundred and fifty-six participants took part in a birdwatching activity, identifying the species that entered their garden during a thirty-minute period. Participants were randomly allocated to the ‘joy’ group, who rated their feeling of joy on seeing each species, or the ‘count’ group, who counted the number of birds of each species. Measures of wellbeing, state anxiety and nature connection were completed before and after the observation period. Both groups had improved wellbeing, anxiety, and nature connection, though decreases in anxiety were greatest for those in the joy group. These results suggest that activating a sense of joy heightens the psychological benefits of watching garden birds. These benefits and the strengthening of nature connections highlight the reciprocal relationship between humans and birds and the importance of actions towards healthy, sustainable urban ecosystems.

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Mobilization of horizontally acquired island 2 is induced in planta in the phytopathogen P ectobacterium atrosepticum SCRI 1043 and involves the putative relaxase ECA 0613 and quorum sensing - Bhanupratap R. Vanga; Pavithra Ramakrishnan; Ruth C. Butler; Ian K. Toth; Clive W. Ronson; Jeanne M. E. Jacobs; Andrew R. Pitman (Environmental Microbiology, 2015)
Summary Integrative and conjugative elements ( ICEs ) contribute to the rapid evolution of bacterial pathogens via horizontal gene transfer of virulence determinants. ICEs have common mechanisms for transmission, yet the cues triggering this process under natural environmental or physiological conditions are largely unknown. In this study, mobilization of the putative ICE horizontally acquired island 2 ( HAI 2), present in the chromosome of the phytopathogen P ectobacterium atrosepticum SCRI 1043, was examined during infection of the host plant potato. Under these conditions, mobilization of HAI 2 increased markedly compared with in vitro cultures. In planta ‐induced mobilization of HAI 2 was regulated by quorum sensing and involved the putative ICE ‐encoded relaxase ECA 0613. Disruption of ECA 0613 also reduced transcription of genes involved in production of coronafacic acid (Cfa), the major virulence factor harboured on HAI 2, whereas their expression was unaffected in the quorum‐sensing ( expI ) mutant. Thus, suppression of cfa gene expression was not regulated by the mobilization of the ICE per se , but was due directly to inactivation of the relaxase. The identification of genetic factors associated solely with in planta mobilization of an ICE demonstrates that this process is highly adapted to the natural environment of the bacterial host and can influence the expression of virulence determinants.

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Relationship Between Six Years of Corn Yields and Terrain Attributes - Thomas C. Kaspar; Thomas S. Colvin; Daniel B. Jaynes; Douglas L. Karlen; David E. James; David W. Meek; Daniel Pulido; Howard Butler (Precision Agriculture, 2003)

Differentiation of a rapidly growing, scotochromogenic, polycyclic-aromatic-hydrocarbon-metabolizing strain of Mycobacterium sp. from other known Mycobacterium species - Fatemeh Rafii; W. Ray Butler; Carl E. Cerniglia (Archives of Microbiology, 1992)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)